Improving Clinical Nurses' Competence through Peer Teaching - Hendra Ari Wibawa; Potawan Witwaranuu (PT.Mantaya Idea Batara, 2025)
Background: Nurses continuously interact with patients and provide interventions according to their needs and responses over a 24-hour period. Given this vital role, clinical nurses must maintain a high level of competency to ensure the quality and safety of patient care. Hospitals are therefore required to establish training programs that address the developmental needs of their staff, aiming to meet a service standard of at least 20 hours of training per year. However, the average training achievement among external employees often falls short, making it essential to explore alternative strategies to enhance learning hours and workforce competencies. One such method is peer teaching. Method: This study employed a descriptive analysis approach. The implementation of peer teaching activities was conducted in several phases: the preparation phase, the implementation phase, and the evaluation phase. Results: The findings revealed that the average pre-test score was 75, while the average post-test score increased to 91. Observations during the process indicated that clinical nurses actively participated in discussions throughout the peer teaching sessions.Discussion: The peer teaching method significantly enhances learning motivation and encourages active student engagement. Rather than passively listening and taking notes, students become directly involved in the learning process, contributing ideas and interacting with peers. This engagement supports improved long-term retention of knowledge.Conclusion: Peer teaching positively influences the improvement of clinical nurses’ competencies. Further in-depth studies are recommended to explore the impact of this method on learning satisfaction.